Designing XR : a rhetorical design perspective for the ecology of human+computer systems - Zakrzewski, Peter (Emerald Publishing Limited, 2022)
The long-standing cultural imperative of augmenting human intellect continues to move ever closer to its full manifestation, described by Marshall McLuhan as an extension of the human nervous system. The escalating blending of immersive technologies with advanced computation has created an emerging domain which increasingly allows socio-technical system makers to produce not only human-computer interactions, but advanced, multi-minded human+computer (H+C) systems. The critical shift toward user immersion within systems of digital information and simulation makes the scale of immersive media's potential impact on human life, culture and well-being unlike that of any previous medium. In Designing XR, Peter (Zak) Zakrzewski presents H+C immersion as a multi-dimensional design problem - a Research Through Design (RTD) zone which addresses the question of: How can transformative design-thinking-based knowledge system complement the existing human-computer interaction (HCI) invention model to contribute to the creation of more participatory, socially viable, and humane immersive media environments? The book lays out a proposal for ushering the creation of ecologically sound augmented mind based on two essential tasks. The first involves a framework for the design, implementation, and iteration of purposeful, multi-minded, participatory immersive H+C systems. The second focuses on the extended reality experience (XRX) design practice that rhetorically invites users to actively engage with immersive systems while fully exercising their autonomy and agency based on informed choice.